APLIKASI KOMIK SEBAGAI MEDIA PEMBELAJARAN - Anip Dwi Saputro (Universitas Muhammadiyah Ponorogo, 2015)
This research aims to: (1) produce a scientific comic instructional media which is good for learning a science in terms of its physical fesibility, design, color, material, images, and text as an introduction to the students discussion, (2) determine the feasibility of scientific comi instructional media. It was a Research and Development (RD), which was done in eigth stages, are(1) Doing the preliminary study and information gathering, (2) Planning, (3) Developing the initial product form, (4) conducting an individual trial, (5) Doing the first revision, (6) Conducting a small group trial, (7) Doing the second revision, (8) Doing a field trial. The subject were the seventh grade students of SMP N 6Ponorogo. The respondents used in this study were 46 students, consisting of 3 validators, 3 students to test one-on-one, 10 students for small group trial, and 30 students for field trial. Aspects accessed were including the media aspect, material aspect, and learning aspect. The data from this study were analized using a descriptive percentage. The result showed that: (1) The quality of media aspect, by the media expert validation, reached an average of 3.87 or in good categories, (2) The material and learning aspect, by material expert validation, reached an average 3.78 or in good categories, and (3) Based on the students assessment on the instructional media aspects, that were physical fesibility, design, color, material, images, and text, obtained a percentage average of 86.9% or in good categories also. It showed that the development product of a scientific instructional media for the seventh grade students of SMP reached the revision stage to be disseminated, then after some revisions it is expected to have a better result to disseminate as an instructional media or learning sources